Teacher Victimisation in Educational Institutions: Analysis of the Legal Environment - Gušauskienė, Marina; Indrašienė, Valdonė; Prakapas, Romas; Railienė, Asta; Sadauskas, Justinas (Pedagogika, 2025)
The article assesses the legal possibilities of protecting teachers from violence in Lithuanian educational institutions. It analyses how the legal framework ensures the right of teachers to protection from violence at work and to assistance. It is concluded that the concept of violence against teachers is not clearly defined in legislation, the legal framework does not sufficiently protect teachers from violence and is more oriented towards the protection of pupils.